2017
DOI: 10.1093/femsec/fix109
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial community dynamics and assembly under long-term land use change

Abstract: We evaluated the bacterial and archaeal community dynamics and assembly in soils under forest, grassland and no-till cropping, using a high-throughput shotgun metagenomics approach. No significant alterations in alpha diversity were observed among different land uses, but beta diversity in grassland was lower than that observed in forest and no-till soils. Grassland communities showed assembly that predominantly followed the neutral model, i.e. high homogenizing selection with moderate dispersion, leading to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
67
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 80 publications
18
67
2
Order By: Relevance
“…We used "metagenomeseq R package [46] to normalize the abundances. For details regarding DNA library preparation, sequencing procedure, and metagenome annotation see [27] (detailed information can also be found in Supplementary Material). Shotgun metagenome data are available at MG-RAST server under the project ID 7830.…”
Section: Sequencing and Bioinformaticsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used "metagenomeseq R package [46] to normalize the abundances. For details regarding DNA library preparation, sequencing procedure, and metagenome annotation see [27] (detailed information can also be found in Supplementary Material). Shotgun metagenome data are available at MG-RAST server under the project ID 7830.…”
Section: Sequencing and Bioinformaticsmentioning
confidence: 99%
“…Although selection could explain, in a certain way, the differences in microbial community assembly and diversifica-tion, empirical and theoretical models have shown that that not only selection but also drift and dispersal processes could be interacting with diversification [14], resulting in differential assembly patterns across soil types, soil fractions, time, and host plant species [25][26][27][28]. However, those processes have been often neglected in ecology studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, belowground biodiversity loss is very likely to have negative effects both on the environment and on the sustainability of agricultural production as microbial functions will be altered (Tardy et al, 2014). Recently, metagenomic approaches have investigated the impact on the composition and structure of soil microbiome of converting semi-deciduous Amazonian rainforest and natural grasslands to arable soils (Mendes et al, 2015;Castañeda and Barbosa, 2017;Goss-Souza et al, 2017;Kroeger et al, 2018). These studies found that arable soils were similar or more diverse than the original ecosystem and that functional redundancy overcomes the ecosystem transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, we provide new evidence that low-disturbance practice promotes deep-soil stability to cope with environmental stress through increasing water and nutrient holding capacity, microbial richness, microbial diversity and ecological functions. According to ecological theory(49, 50), microbial community assembly in the CT treatment was mainly based on deterministic processes and significantly influenced by environmental stress and fertilizer nitrogen. Stover mulching might alter these processes through deeper roots affecting the vertical heterogeneity in resource availability(4).…”
Section: Discussionmentioning
confidence: 99%